Business process changes on the implementation of artificial intelligence - Do Amaral Adorno, Oscar (2021)
The digital transformation process is a phenomenon that will affect all organizations. In companies that have already started the digital transformation, Artificial Intelligence (AI) initiatives are begging to appear and will have a competitive impact on organizations leading digital transformation. In businesses that have already started this process, AI solutions have begun to appear. Projects on digital transformation pose new challenges and cause organizational changes in business, operational and administrative processes. Our objective was to identify changes, potential effects, and impacts of AI technologies on business processes, transformation dynamics, organizational structures, and management. This qualitative research examined the cases of five large companies with a high degree of maturity in digital transformation and innovation: one Brazilian company and four multinational subsidiaries based in Brazil. Their industries were telecom & technology, professional services, logistics services, chemical and financial services. Companies have been engaged in a long-term digital transformation and in the AI journey. Different companies have distinct organizational structures for portfolio management and project implementation. Their challenges and changes were identified through content analysis with a semi-structured interview protocol. Publicly available data and data provided by the companies were collected. The main reported challenges were measuring business value, lack of people with the required capabilities, change management issues, cultural resistance, and integration with existing processes and systems. The most affected business processes included Information Technology & Human Resources services, document analysis, and supplier registration (internal processes), and customer service (external processes). Improving professional and academic work in this field has great relevance at this moment, as professionals and scholars have begun to understand the transformative potential of AI technologies in our society.